Cuarto informe sobre delitos y violencias en la provincia de Buenos Aires 2009-2021 - Cabral, Paz (Informes FaHCE, 2022)
Fourth Report on Crime and Violence in the Province of Buenos Aires 2009-2021: This report was prepared by the team of the Observatory on Security Policies of the Province of Buenos Aires (Observatorio de Políticas de Seguridad de la Provincia de Buenos Aires, OPS), based at the Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata. This work provides statistical information on trends in lethal and highly lethal violence during the period 2009-2021, both in the province of Buenos Aires and in judicial districts of Greater Buenos Aires. In addition to presenting the dynamics of the total number of preliminary criminal investigations, data on intentional, attempted and culpable homicides, minor injuries, threats, robberies, crimes against sexual integrity and the crime of infringement of Law 23,737 (related to drug possession and trafficking) are analyzed. An analysis of intentional homicides broken down by judicial districts is also included, which shows the territorial heterogeneity of the province.